Konseling Kelompok untuk Mengurangi Perilaku Bullying Pada Siswa UPT SMPN 9 Gresik (International Forum of Researchers and Lecturers, 2024)
Bullying is a serious problem in the school environment that can have a negative impact on students' psychological and social development. This study aims to explore the effectiveness of group counseling in reducing bullying behavior among UPT SMPN 9 Gresik students. Group counseling is used as an intervention approach that focuses on improving empathy, positive communication, and emotional control among students. This research method involves a quantitative approach, an experimental method with one group pretest-posttest desaign to measure changes in student behavior before and after participating in group counseling. The results showed that group counseling was able to significantly reduce the frequency of bullying behavior. Through counseling activities, students learn to understand the negative impact of bullying, build better social skills, and create a safer and more harmonious school environment. These findings suggest that group counseling